Metastability in Senescence. Issue 7 (July 2017) - Naik, Shruti; Banerjee, Arpan; Bapi, Raju S.; Deco, Gustavo; Roy, Dipanjan
Abstract : The brain during healthy aging exhibits gradual deterioration of structure but maintains a high level of cognitive ability. These structural changes are often accompanied by reorganization of functional brain networks. Existing neurocognitive theories of aging have argued that such changes are either beneficial or detrimental. Despite numerous empirical investigations, the field lacks a coherent account of the dynamic processes that occur over our lifespan. Taking advantage of the recent developments in whole-brain computational modeling approaches, we hypothesize that the continuous process of aging can be explained by the concepts of metastability − a theoretical framework that gives a systematic account of the variability of the brain. This hypothesis can bridge the gap between existing theories and the empirical findings on age-related changes. Trends: Tracking dynamic changes in metastability across lifespan enables relating age-related structural and functional findings to theories of cognitive aging. Metastability can be studied using dynamic functional connectivity rather than current static approaches. Whole-brain computational models are required to test the hypothesis that aging affects the dynamics of the brain at different timescales.